The role of symbolic capital and symbolic violence in shaping social hierarchies through digital consumption and production in Roblox online game - Oktavianingtyas, Irmawati; Rusadi, Udi; Jamalullail, Jamalullail; Napitupulu, Frenki (Universitas Bunda Mulia, 2025)
This study investigates how symbolic capital is accumulated and how symbolic violence operates to legitimize economic disparities within the digital society of Roblox. Using Pierre Bourdieu’s concepts of symbolic capital and symbolic violence, this research explores how digital consumption and production practices contribute to the construction and legitimization of social hierarchies. A qualitative approach using case study method was adopted, with data collected through in-depth interviews, participant observation, and document analysis. The findings reveal that symbolic capital in Roblox is accumulated as prestige and reputation. Prestige is gained through the ownership of premium items and exclusive memberships that signify wealth and social status. Reputation is achieved through social influence and recognition as game developers and creators, reinforced by verified badges and symbolic awards. The study further reveals that symbolic violence operates through four mechanisms: social status differentiation, internalization of social hierarchies, justification of economic disparities, and reproduction of social hierarchies. These mechanisms differentiate players based on symbolic capital, leading to internalized social hierarchies that justify economic inequalities as logical social distinctions. This conceals power dynamics and motivates players to participate willingly in economic practices that sustain social stratification within the digital society of Roblox.